2017
DOI: 10.1111/imb.12313
|View full text |Cite
|
Sign up to set email alerts
|

Cycle affects imidacloprid efficiency by mediating cytochrome P450 expression in the brown planthopper Nilaparvata lugens

Abstract: Circadian clocks influence most behaviours and physiological activities in animals, including daily fluctuations in metabolism. However, how the clock gene cycle influences insects' responses to pesticides has rarely been reported. Here, we provide evidence that cycle affects imidacloprid efficacy by mediating the expression of cytochrome P450 genes in the brown planthopper (BPH) Nilaparvata lugens, a serious insect pest of rice. Survival bioassays showed that the susceptibility of BPH adults to imidacloprid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Each treatment was performed in triplicate. qRT-PCR also used a previously described method [49]. The primers used for dsRNA preparation and real-time PCR are listed in Table S5.…”
Section: Methodsmentioning
confidence: 99%
“…Each treatment was performed in triplicate. qRT-PCR also used a previously described method [49]. The primers used for dsRNA preparation and real-time PCR are listed in Table S5.…”
Section: Methodsmentioning
confidence: 99%
“…The study by Kang et al provides the evidence that the circadian cycles of Nilaparvata lugens affect the effectiveness of imidacloprid. The scientists explain this by two peaks in the expression of cytochrome P450 genes during the day [Kang et al 2017]. When studying the effect of deltamethrin on Anopheles gambiae mosquitoes, it was shown that among the metabolic detoxification enzymes there are those that depend on the time of day (glutathione-S-transferases) and have constant activity (oxidases and esterases) [Balmert et al 2014].…”
Section: Annual and Circadian Rhythms Of Organism Activitymentioning
confidence: 99%